An Innovative Approach for Modeling Ultrasonic-assisted Drying - Adiyta Putranto; Xiao Dong Chen (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Drying is a simultaneous heat and mass transfer process which involves significant energy consumption. For sustainable processing practice, ultrasonic-assisted drying is often implemented. In order to assist in process design and optimization, a physically-meaningful drying model is useful. The REA (reaction engineering approach), which has been shown to be accurate to model several challenging drying cases, is implemented here to model the ultrasonic-assisted drying with various intensities. The relative activation energy (ΔEv,b) generated from one accurate drying experiment is used to model the ultrasound-assisted drying with various intensities. The results of modeling match very well with the experimental data. The REA is accurate to model the ultrasonic-assisted drying under various intensities (i.e. 8, 12, 21, 29 and 31 kW/m3). The mechanisms of ultrasonic-assisted drying can be explained well by the REA. A landmark for process intensification of drying process has been set up by the REA. The model can be readily adopted in industrial settings for process design and optimization.